Study on The Acceleration of Economic Recovery for Makassar City - Anas Iswanto Anwar; Andi Harmoko Arifin; Sri Undai Nurbayani; Rakhmat Nurul Prima Nugraha; Abdul Rahman; Hasan Basri Umar (International Business and Accounting Research Journal, 2022)
This study aims to identify the leading sectors of the City of Makassar in order to realize the acceleration of the economic recovery of the City of Makassar on a strong and sustainable sector basis. By using the analysis method Static Location Quotient, Dynamic Location Quotient, Growth Ratio model and overlay. The main data source in this study is ADHK GRDP from 2015 to 2021 which is available at the Central Bureau of Statistics (BPS) for Makassar City and South Sulawesi Province. The results of the LQ analysis show that only 4 sectors are not included in the base sector including the Agriculture, Forestry and Fishing Sectors; Electricity and Gas; Transportation and Storage. While the results of the DLQ analysis show four sectors with fast growth rates and are leading sectors from the results of the LQ analysis, namely Transportation and Storage; Public Administration and Defence, Compulsory, Social Security; Human Health and Social Work Activities. As an effort to accelerate economic recovery, sectors that were superior according to LQ calculations, prospective according to DLQ, and included in MRP and overlay classification were selected, namely Manufacturing and Accomodation, and Food Service Activities.